Paris after Trump: An inconvenient insight - Christoph Böhringer; Thomas F. Rutherford (University of Oldenburg, Department of Economics, 2017)
With his announcement to pull the US out of the Paris Agreement US President Donald Trump has snubbed the international climate policy community. Key remaining parties to the Agreement such as Europe and China might call for carbon tariffs on US imports as sanctioning instrument to coerce US compliance. Our analysis, however, reveals an inconvenient insight for advocates of carbon tariffs: Given the possibility of retaliatory tariffs across all imported goods, carbon tariffs do not constitute a credible threat for the US. A tariff war with its main trading partners China and Europe might make the US worse off than compliance to the Paris Agreement but China, in particular, should prefer US defection to a tariff war.
Keywords: Q58; D58; 330; Paris Agreement; US withdrawal; carbon tariffs; optimal tariffs; tariff war; computable general equilibrium